Pure Laparoscopic vs. Open Right Hepatectomy in Living Liver Donors: Bench-Surgery Time - Hong, Kwangpyo; Hong, Suk Kyun; Han, Eui Soo; Suh, Sanggyun; Hong, Su young; Lee, Jeong-Moo; Choi, YoungRok; Yi, Nam-Joon; Lee, Kwang-Woong; Suh, Kyung-Suk (Frontiers in Surgery, 2021)
Background: Recently, there have been several reports on pure laparoscopic donor right hepatectomy (PLDRH), but the effect of pure laparoscopy on bench surgery has not been evaluated. This study aimed to compare bench-surgery time between PLDRH and conventional donor right hepatectomy (CDRH). Methods: We retrospectively reviewed the medical records of 758 live liver donors between January 2012 and December 2019. We divided the patients into two groups: between January 2012 and September 2015, when we exclusively performed CDRH, and between March 2016 and December 2016, when PLDRH was standardized. We excluded all other types of graft donor hepatectomy, laparoscopic assisted donor hepatectomy, and cases with no recorded data. Results: In total, 267 donors were included in the PLDRH group and were compared with 247 donors in the CDRH group. Similar proportions of graft vascular variations were observed between the two groups. The mean bench-surgery time was longer in the PLDRH group than in the CDRH group (49.3 ± 19.9 vs. 39.5 ± 17.5 min; P < 0.001). Conclusion: The bench-surgery time was longer in the PLDRH group than the CDRH group, regardless of whether the vascular network was reconstructed. Expertise in bench-surgery as well as donor surgery and recipient surgery is mandatory for PLDRH to be safe and feasible.